Integral representation of even positive-definite functions of one variable - Lopotko, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain an integral representation of even positive-definite functions of one variable for which the kernel [k_1(x + y) + k_2 (x − y)] is positive definite.